News media framing of the Murray–Darling Basin ‘water theft’ controversy - Clifford, Katrina (Journal of criminology, 2021)
An Australian Broadcasting Corporation (ABC) Four Corners investigation, screened on free-to-air television on 24 July 2017, revealed a series of improper conducts pertaining to the Murray?Darling Basin river system. The journalistic exposé included allegations of water theft, questionable compliance decisions and collusion between water regulators and irrigation lobbyists. This interdisciplinary study explores the revelations and their framing in a sample of state and national media reports about the ?water theft? controversy and its fallout. It compares these with the normative frames adopted by critical green criminology, which views the allegations at the heart of the Murray?Darling Basin controversy in terms of state-corporate interests, industry capture of regulators and the notion that water ?theft? constitutes a ?crime? because of the environmental harm that results from excessive water extraction. This article presents the findings of the study, which elaborate on the impacts of media framing of crimes of the powerful (such as large agricultural companies and state government agencies), including the shaping of public understandings of environmental matters.